(untitled) (International Engineering Journal For Research & Development, 2020)
The article deals with the theoretical aspects of the study of psychological preparedness of teachers to innovative activity It analyzes the psycho-pedagogical works devoted to the study of the given phenomenon and makes an attempt to single out the structure of psychological preparedness of teachers to innovative activity, which will make it possible to define and work out psycho-pedagogical technologies of its formation in practical teachers. Also touched upon are the concepts of the level of pedagogical activity that requires a restructuring of the motivational sphere of the teacher's personality, his value orientations, goals, attitudes, hierarchy of external and internal incentives, orientation, claims, and interests